MORINGA OLEIFERA LEAF AS A POTENTIAL ANTITHROMBOTIC AGENT: AN IN VITRO EVALUATION - Ayanti, Bio Putri; Nurbidayah, Nurbidayah; Amalia, Nurul; Azzahra, Syafina; Amini, Amalia (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2025)
Cardiovascular disease (CVD) is a major cause of morbidity and mortality worldwide, one of which is triggered by an imbalance between fibrin formation and fibrinolysis processes, leading to fibrin accumulation that can lead to thrombosis. Commercial thrombolytic agents are currently widely used, but their use is known to cause serious side effects often and have limited effectiveness. This gap encourages initial screening of natural materials as an effort to explore the potential of new thrombolytic agents in the future. This study aims to evaluate the potential of Moringa oleifera leaf filtrate at concentrations of 25%, 50%, 75%, and 100% as an antithrombotic agent through qualitative identification of secondary metabolites and testing of thrombolytic activity and anticoagulant ability in vitro. The results showed that Moringa leaf filtrate at a concentration of 25% was able to lyse blood clots by 60%, compared to the positive control nattokinase (82%), with a relative effectiveness of 71.7%. In vitro anticoagulant activity testing showed an extension of blood clotting time from 10 minutes (control) to 35 minutes in the treatment. ANOVA analysis showed a significant difference between concentrations (p < 0.05). These findings support the initial potential of this natural product as a candidate antithrombotic agent and provide a scientific basis for further research.